Prevalence, Circumstances, and Risk Factors of Falls Among Community Dwelling Members of University of the Third Age - Ashari, Asmidawati; Hamid, Tengku Aizan; Hussain, Mohd Rizal; Ibrahim, Rahimah; Hill, Keith D. (Frontiers in Public Health, 2021)
Objective: Study aimed to identify the prevalence of falls and associated contributory factors among older Malaysians. Methods: A cross sectional study among community dwelling older adults aged 50 years and above. Self-administered questionnaires on history of falls in the previous 12 months, physical assessment and computerized and clinical measures of balance were assessed on a single occasion. Results: Forty nine (31.0%) participants fell, with 4.4% reported having multiple falls within the previous twelve months. Slips were the most prevalent cause of falls, accounting for 49% of falls. More than half (54.5%) of falls occurred in the afternoon while participants walked inside the home (32.7%), outside home (30.6%), and 36.7% were in community areas. More than half of respondents were identified as having turning instability. Step Test, turn sway, depression, physical activity level and edge contrast sensitivity were significantly worse for fallers (p<0.05). Multiple regression analysis showed that turning performance were significantly associated with falls risk, accounting for 72% of the variance of risk factors. Conclusion: Falls are common among community dwelling older Malaysians. The findings provide information of falls and falls risk factors among community dwelling older adults in Malaysia. Future intervention studies should target locally identified falls risk factors. This study has highlighted the importance of instability during turning as an important fall risk factor.